Sweltsa onkos - Stark, Bill P.; Kondratieff, Boris C.; Kirchner, Ralph F.; Stewart, Kenneth W. (Zenodo, 2011)
Sweltsa onkos (Ricker) (Figs. 21-25) Alloperla onkos Ricker, 1935:256. Holotype ♂ (Royal Ontario Museum), Ontario, Dufferin Co., Horning’s Mills, headwaters of Pine River Material examined. QUEBEC PROVINCE: Diable Parc, Mont-Tremblant, Lac Monroe, 8 June 1997, B.C. Kondratieff, R. W. Baumann, 20♂, 1 pharate larva (CSU). River Rems, north of Baie St. Paul, 9 June 1997, B.C. Kondratieff, R. W. Baumann, 13♂, 2 larval skins (CSU). Mature larva. Body length 7.5-8.5 mm. General color brown, abdomen chestnut brown; body without distinctive pattern except underlying adult features in pharate individuals. Thorax and abdomen covered with abundant dark clothing hairs. Pronotum bearing ca. 20 anterolateral setae, and ca. 19 posterolateral setae; both rows extend to near median suture (Fig. 21). Mesonotum bearing ca. 13 outer marginal setae and a few inner marginal setae (Fig. 22). Foreleg with sparse femoral and more extensive tibial fringe setae; femora with ca. 5 long thick setae on dorsal margin and ca. 9 on ventral margin (Fig. 23); tibiae bearing 3- 4 long thin outer marginal setae and ca. 5 inner marginal thick setae. Abdominal tergum 8 with posterior fringe complete; mesally fringe includes mixed thin and thick setae (Fig. 24); lateral intercalary setal cluster includes ca. 14 thick setae. Cerci with ca.14-15 segments; long dorsal setae in apical segmental whorls about as long as two segments (Fig. 25). Comments. Sweltsa onkos is a common species that occurs from Atlantic Canada, Newfoundland, Ontario and Quebec south to Virginia (Kondratieff & Kirchner 2009). Fiance (1977) provides a habitus drawing of larvae of this species and several figures showing setal arrangements for several larval body parts, based on material from Bear Brook, New Hampshire. These figures are in general agreement with our data derived from Quebec specimens, except the length of cercal setae appear shorter, the lateral pronotal setae much more extensive, and dorsal femoral fringe setae more numerous in Fiance’s (1977) illustrations. Larvae appear most similar to the sympatric S. naica but the meso and metanotum are densely covered with long clothing hairs (Fig. 22). See additional comments above for S. hoffmani, S. lateralis and S. naica . : Published as part of Stark, Bill P., Kondratieff, Boris C., Kirchner, Ralph F. & Stewart, Kenneth W., 2011, Larvae Of Eight Eastern North American Sweltsa (Plecoptera: Chloroperlidae), pp. 51-64 in Illiesia 7 (4) on pages 57-59, DOI: 10.5281/zenodo.4760403 : {"references": ["Ricker, W. E. 1935. New Canadian perlids (part II). Canadian Entomologist, 67: 256 - 264.", "Kondratieff, B. C. & R. F. Kirchner. 2009. A new species in the Sweltsa onkos complex (Plecoptera: Chloroperlidae). Pp. 295 - 300 in Roble, S. M. & J. C. Mitchell [editors]. A lifetime of contributions to Myriapodology and the natural history of Virginia: A festschrift in honor of Richard L. Hoffman's 80 th birthday. Virginia Museum of Natural History Special Publication No. 16. Martinsville, Virginia.", "Fiance, S. B. 1977. The genera of eastern North American Chloroperlidae (Plecoptera): Key to larval stages. Psyche, 84: 308 - 316."]}